THE STUDY OF THE EFFECTIVENESS OF ANTIHYPOXIC PROPERTIES OF CERTAIN COMPOUNDS OF VARIOUS ACTION MECHANISMS ON HEMIC HYPOXIA MODELS (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
The article presents experimental data on the effectiveness of drugs that could stimulate the start of metabolic adaptation during the development of methemoglobinemia. The modeling of this type of hemic hypoxia led to the disruption of antioxidant protection, resulting in a rather significant decrease of superoxide dismutase and catalase (primary antioxidant enzymes) in the blood plasma of tested animals. We have established that anti-hypoxic activity was higher with the use of mexidol compared to the use of tocopherol. The differences in the indicators can perhaps be explained by the different mechanisms of action of the used antioxidants. The state of methemoglobinemia has also led to increased concentrations of medium-size molecules in the blood plasma. The use of mexidol and tocopherol did not show any significant effect on normalization.
Keywords: anti-hypoxic activity; hemic hypoxia; mexidol; acute hypoxia, blood clotting indices, tocopherol